2022
DOI: 10.1200/jco.22.00227
|View full text |Cite
|
Sign up to set email alerts
|

COAST: An Open-Label, Phase II, Multidrug Platform Study of Durvalumab Alone or in Combination With Oleclumab or Monalizumab in Patients With Unresectable, Stage III Non–Small-Cell Lung Cancer

Abstract: PURPOSE Durvalumab significantly improves overall survival for patients with unresectable stage III non–small-cell lung cancer and no progression after concurrent chemoradiotherapy (cCRT). Building upon that standard of care, COAST is a phase II study of durvalumab alone or combined with the anti-CD73 monoclonal antibody oleclumab or anti-NKG2A monoclonal antibody monalizumab as consolidation therapy in this setting. METHODS Patients with unresectable stage III non–small-cell lung cancer, Eastern Cooperative O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
99
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(117 citation statements)
references
References 21 publications
(58 reference statements)
1
99
0
Order By: Relevance
“…All-grade rates of pneumonitis were similar in the three arms (18.6%, 16.4% and 16.7%, respectively) as well as the treatment discontinuation rates (15.3%, 14.8% and 16.7%, respectively). 35 Although durvalumab arm in COAST trial underperformed compared to the PACIFIC trial, mainly related to different patient characteristics, the results of COAST trial support that combination approaches are feasible, safe and may in the future potentially shift again the prognosis of patients in this setting. Therefore, results of COAST trial support further evaluation of these combinations in the currently recruiting phase III PACIFIC-9 trial (NCT05221840).…”
Section: Crossing the Borders Of Pacificmentioning
confidence: 98%
See 2 more Smart Citations
“…All-grade rates of pneumonitis were similar in the three arms (18.6%, 16.4% and 16.7%, respectively) as well as the treatment discontinuation rates (15.3%, 14.8% and 16.7%, respectively). 35 Although durvalumab arm in COAST trial underperformed compared to the PACIFIC trial, mainly related to different patient characteristics, the results of COAST trial support that combination approaches are feasible, safe and may in the future potentially shift again the prognosis of patients in this setting. Therefore, results of COAST trial support further evaluation of these combinations in the currently recruiting phase III PACIFIC-9 trial (NCT05221840).…”
Section: Crossing the Borders Of Pacificmentioning
confidence: 98%
“…The evaluation of efficacy of consolidation ICI in PD-L1-negative NSCLC can be hindered by the small sample size as PD-L1 status was not required for enrollment in majority of trials, as well as by the post hoc analysis or exploratory analysis regarding the efficacy according to the PD-L1 status. 23 , 35 Although the PACIFIC-R study reported that durvalumab was feasible in PD-L1-negative tumors, the median PFS was shorter than PD-L1 ⩾1% tumors, 31 raising the issue of optimal consolidation approach in PD-L1-negative NSCLC.…”
Section: Challenges In Unresectable Nsclcmentioning
confidence: 99%
See 1 more Smart Citation
“…COAST is a phase 2 trial that randomized in a 1:1:1 manner patients between durvalumab alone or in association with oleclumab, an anti-CD73 monoclonal antibody, or monalizumab, an anti-NKG2A monoclonal antibody, for up to 12 months of treatment. Median PFS was 6.3 months for durvalumab alone, 15.1 months (HR = 0.65) for the durvalumab + monalizumab arm, and not reached (HR = 0.44) for durvalumab + oleclumab [ 91 ]. These first results have to be analyzed with caution as the durvalumab alone arm compares poorly with the results of the PACIFIC trial.…”
Section: Therapeutic Approaches To Overcome Radioresistance In Nsclcmentioning
confidence: 99%
“…As a result, monalizumab is now being studied in multiple clinical trials (NCT04307329, NCT04590963, NCT05221840, and NCT05061550) to increase the proportion of patients responding to ICI. The combination of monalizumab with the anti-EGFR antibody, cetuximab, or with the anti-PD-L1 antibody, durvalumab, has led to encouraging responses in a subset of patients with head and neck cancer squamous cell cancer (HNSCC), colorectal cancer (CRC) and non-small cell lung cancer (NSCLC) 13,[18][19][20][21] . The responses observed to combination mAb therapy are superior to monotherapy with monalizumab (NCT02459301).…”
Section: Introductionmentioning
confidence: 99%